МІЖНАРОДНО-ПРАВОВІ СТАНДАРТИ У СФЕРІ ЗАБЕЗПЕЧЕННЯ ПРАВ ГРОМАДЯН, ЗАСУДЖЕНИХ ДО ПОЗБАВЛЕННЯ ВОЛІ: ПОНЯТТЯ, ОСОБЛИВОСТІ, ФУНКЦІЇ - Почанська, Олена Сергіївна (SUPREMANCE OF LAW, 2018)
The content of the notion «international-legal human rights standards» is reveal. Analyses of contemporary scientific approaches to understanding of the specific features of international standards for the treatment of prisoners were conducted. The main functions of international-legal standards which ensuring the rights of persons condemned to imprisonment are determined, and their content is described.